In the Trenches: A Hands-on Pedagogical Approach to Teaching Data Collection Skills in Terrorism Studies - Carthy, Sarah L. (Perspectives on terrorism, 2025)
The burgeoning availability of open-source information on individuals who have been radicalised offers new opportunities to build, expand, and disaggregate rich databases on the characteristics of the phenomenon. However, this type of open-source data collection can be challenging to execute reliably, particularly when research teams include coders of varying skill levels. As the study of terrorism in higher education becomes increasingly formalised, the authors describe a scaffolded pedagogical approach to teaching and assessing the skill of data collection, one which formally integrated database creation into a master’s level course on the topic of terrorism. As the authors reflect on field-wide challenges, including conceptual ambiguities which can prompt unreliable coding, methods for assessing acquired skills and competencies are also examined. In this way, it is hoped that this research note will contribute to efforts to advance the next generation of terrorism scholars, as well as support other educators seeking to incorporate authentic learning experiences into higher education courses.